EFFECT OF OPERATING CONDITIONS ON PERFORMANCE AND EMISSIONS OF A DIESEL ENGINE OPERATED WITH DIESEL-HYDROGEN BLEND (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Hydrogen is a clean fuel for internal combustion engines since it produces only water vapor and nitrogen oxides when it burns. In this research, hydrogen is used as a blending fuel with diesel to reduce pollutants emission and to improve performance. It is inducted in the inlet manifold, of a single cylinder, four stroke, direct injection, water cold diesel engine, type (Kirloskar). Hydrogen blending is done on energy replacement basis. A special electronic unit is designed and fabricated to control hydrogen blending ratio. The maximum achieved ratio is 30% of input energy and beyond that engine operation becomes unsatisfactory when the air temperature is 20 oC and injection timing of -35o CA which represent the first part of this work. Inlet air heating system is built and added in the experimental work. The heating system allows to increase the air temperature up to 100 oC. A heating of air to 60 oC with injection timing of -30o CA and 55% of hydrogen blending is executed in the second part of this study. Tests are done with 17.5 compression ratio and 1500 rpm. The brake specific fuel consumption is reduced by 29% and 46%, the engine thermal efficiency is increased with 16% and 21% for the 1st and 2nd part respectively. The pollutant emissions of carbon oxides, UHC, and smoke opacity are dramatically decreased by 19.5%, 13%, and 45% respectively for the 1st part and 41%, 38% and 65.6% for the 2nd part while NOx emission is increased by 10% and 25% for the 1st and 2nd part respectively.